Nutritional interventions to improve neurophysiological impairments following traumatic brain injury: A systematic review. Issue 2 (26th October 2020) - McGeown, Joshua P.; Hume, Patria A.; Theadom, Alice; Quarrie, Kenneth L.; Borotkanics, Robert
Abstract: Traumatic brain injury (TBI) accounts for significant global health burden. Effects of TBI can become chronic even following mild injury. There is a need to develop effective therapies to attenuate the damaging effects of TBI and improve recovery outcomes. This literature review using a priori criteria (PROSPERO; CRD42018100623) summarized 43 studies between January 1998 and July 2019 that investigated nutritional interventions (NUT) delivered with the objective of altering neurophysiological (NP) outcomes following TBI. Risk of bias was assessed for included studies, and NP outcomes recorded. The systematic search resulted in 43 of 3, 748 identified studies met inclusion criteria. No studies evaluated the effect of a NUT on NP outcomes of TBI in humans. Biomarkers of morphological changes and apoptosis, oxidative stress, and plasticity, neurogenesis, and neurotransmission were the most evaluated NP outcomes across the 43 studies that used 2, 897 animals. The risk of bias was unclear in all reviewed studies due to poorly detailed methodology sections. Taking these limitations into account, anti‐oxidants, branched chain amino acids, and ω‐3 polyunsaturated fatty acids have shown the most promising pre‐clinical results for altering NP outcomes following TBI. Refinement of pre‐clinical methodologies used to evaluate effects of interventions on secondary damage of TBI would improve the likelihood of translation to clinical populations.